Chemical investigation on the male flowers of Carica Papaya using acid-base separation process - Hossain, Md Delwar; Nahar, Shamsun; Ahmad, Mesbah Uddin; Saha, Koushik (Journal of Bangladesh Academy of Sciences, 2022)
Five long-chain hydrocarbons and a new brominated nitrogenous terpenoid were isolated from the acidic and basic fraction respectively of an ethanol extract of the male flowers of Carica Papaya for the first time. It was collected from Bangladesh Agriculture Development Corporation, Gazipur. J. Bangladesh Acad. Sci. 45(2); 181-186: December 2021